A method for recycling waste rigid polyurethane foam to prepare polyether polyol

By catalyzing the addition of epoxides to polyurethane foam alcohol dissolution products in the two-step method, the problems of high amine value and wide molecular weight distribution of oligomer polyol mixtures in the prior art are solved, and high-quality polyether polyol regeneration is achieved. Can be used to prepare high-performance polyurethane rigid foam.

CN113896880BActive Publication Date: 2025-02-18WANHUA CHEMICAL (NINGBO) CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111267744.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-02-18
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

The oligomeric polyol mixture obtained by the chemical recycling method of existing polyurethane foams has problems such as high amine value and wide molecular weight distribution, which leads to poor quality of reuse products and is difficult to directly use in the high-end polyurethane foam industry.

Method used

The method of catalyzing the addition of epoxides to polyurethane foam alcoholylation products is adopted in two steps. First, the polymerization of the alcoholylation products and epoxides is used to catalyze the polymerization of the alcoholylation products and the epoxides, and converted into a mixture of oligopolymer polyols with low amine values; then phosphazenes are used. The catalyst preferentially catalyzes the polymerization of low molecular weight polyols and concentrates the molecular weight distribution.

Benefits of technology

Effectively reduce the broadness of the amine value and molecular weight distribution in the recovered product, so that the product quality of regenerated polyether polyol can be improved, and can be directly used to prepare high-quality polyurethane rigid foam, with low thermal conductivity and high compression strength. advantage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003327467430000131
    Figure BDA0003327467430000131
  • Figure BDA0003327467430000141
    Figure BDA0003327467430000141
Patent Text Reader

Abstract

The present invention provides a method for preparing polyether polyol by recycling waste rigid polyurethane foam. The method comprises: crushing the recycled rigid polyurethane foam material into particles, compounding with an alcoholysis agent and an alkali into an alcoholysis solution, and heating to obtain an alcoholysis product; filtering the alcoholysis product and transferring it into a reactor, adding an alkali metal catalyst, adding an epoxide after dehydration to carry out a polymerization reaction, cooling, adding a phosphazene catalyst, and continuing to add an epoxide after heating to carry out a polymerization reaction to obtain a high molecular weight polyether polyol; cooling the polyether polyol, adding a neutralizer and an adsorbent, dehydrating after a neutralization reaction, and filtering to obtain a target polyether polyol. The present invention overcomes the shortcomings of a wide molecular weight distribution and a high amine value of the alcoholysis product, and the polyurethane foam obtained by the recycled product has the characteristics of low thermal conductivity and high compression strength, which can realize high-quality recycling of materials in the polyurethane industry and effectively reduce the impact of polyurethane waste on the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of recycling and reusing waste polyurethane products, and specifically relates to a method for preparing polyether polyol by recycling waste rigid polyurethane foam. Background Art

[0002] Polyurethane foam is widely used in many fields such as construction, automobile transportation, cold chain, and pipeline insulation materials due to its excellent physical and mechanical properties. The application scope of polyurethane foam is constantly expanding, and the output is growing, but at the same time, the waste polyurethane foam is also increasing day by day, and how to deal with it is also a big problem. The traditional treatment method for waste polyurethane foam is incineration and landfill, but the incineration process will produce a large amount of toxic and harmful gases such as NO 2 , hydrocyanic acid (HCN), polluting the environment; landfilling will occupy a large amount of land resources, and the extremely long degradation time will also cause serious damage to the soil. Therefore, neither landfilling nor incineration is a suitable treatment method, which is neither environmentally friendly nor economical. Physical recycling such as simple crushing and reprocessing as filler can only be applied to low-end applications, and the processing capacity is also limited.

[0003] Chemical recovery can effectively avoid the above problems. Chemical recovery methods mainly include alkaline hydrolysis, aminolysis, hydrolysis and alcoholysis. At present, the more mature chemical recovery method in industry is alcoholysis. The recovered liquid obtained by alcoholysis mainly includes hydroxyl-terminated oligomers (containing benzene rings and carbamate structures) and unreacted alcoholysis agents (polyol small molecules). However, there are still some problems with the oligomer polyol mixture obtained by this method, such as: the oligomer mixture obtained by alcoholysis will inevitably be mixed with some primary amines, secondary amine compounds, moisture, and may even contain some solid inorganic filler particles. At the same time, because oligomers and small molecule polyols coexist in alcoholysis products, the molecular weight distribution is relatively wide, and the average molecular weight is relatively low. When it is reused in the polyurethane foam industry, the product quality is poor, and it can only be used or applied in low-end fields after being mixed with normal polyol products.

[0004] At present, there have been relevant reports on the recovery of polyurethane foam alcoholysis. The polyurethane chemical recovery method mentioned in CN102196279A patent does not mention the above problems. The product of a waste polyurethane elastomer recovered mentioned in CN104672414A is directly used in low-end thermal insulation materials. In the polyurethane foam chemical recovery method mentioned in CN105399985A patent, anhydride and phthalic anhydride deamination agents are added to solve the problem of high amine value of the recovered product, but the patent does not involve the solution to the problem of wide molecular weight distribution of the recovered product. In order to make the oligomer polyols recovered from polyurethane foam better reused in the polyurethane industry and realize the green and high-quality recycling of waste polyurethane foam, the above problems must be effectively solved. Summary of the invention

[0005] The purpose of the present invention is to improve the above-mentioned problems and provide a method for recycling waste rigid polyurethane foam to prepare polyether polyols. The polyurethane foam recycling method of the present invention has the advantages that the recycled product has a low amine value and a concentrated molecular weight distribution, and the foam products made from the recycled product have a low thermal conductivity and high compression strength, and can achieve high-quality recycling of polyurethane foam.

[0006] Different from the direct use or blending of polyethers regenerated from polyurethane foam alcoholysis, the present invention adopts a two-step catalytic polyurethane foam alcoholysis product addition epoxide method, firstly, an alkali metal catalyst is used to catalyze the polymerization of amine substances, residual alcoholysis agent, hydroxyl-terminated oligomers (containing benzene rings and carbamate structures) and epoxides in the alcoholysis product to convert them into an oligomer polyol mixture with a low amine value; then, the selective phosphonitrile catalyst is used to preferentially catalyze the polymerization of low molecular weight polyols to make the molecular weight of the regenerated polyether polyol product more concentrated.

[0007] Compared with other polyurethane foam alcoholysis regeneration technologies, the regenerated polyether polyol prepared by this method effectively reduces the adverse effects of residual alcoholysis agents and amine substances in the recovered products on the subsequent foaming process, can be directly reused to prepare polyurethane rigid foam, and fully utilizes the rigid structures such as benzene rings in the recycled polyether to improve the heat resistance and compression strength of the foam products.

[0008] The present invention achieves the above-mentioned invention object through the following technical solutions:

[0009] A method for recycling waste rigid polyurethane foam to prepare polyether polyols, the method comprising the following steps:

[0010] S1: crushing the recovered rigid polyurethane foam material into particles, compounding with an alcoholysis agent and an alkali to form an alcoholysis solution, and heating to obtain an alcoholysis product;

[0011] S2: filtering the alcoholysis product and transferring it to a reactor, adding an alkali metal catalyst, adding epoxide after dehydration to carry out polymerization reaction, cooling, then adding catalyst A, heating and continuing to add epoxide to carry out polymerization reaction to obtain a high molecular weight polyether polyol;

[0012] S3: Cooling the polyether polyol, adding a neutralizing agent and an adsorbent, dehydrating after neutralization reaction, and filtering to obtain the target polyether polyol.

[0013] The above-mentioned two-step catalytic polyurethane foam alcoholysis product addition epoxide method first uses an alkali metal catalyst to catalyze the polymerization of amine substances, residual alcoholysis agent, hydroxyl-terminated oligomers (containing benzene rings and carbamate structures) in the alcoholysis product with epoxides to convert them into an oligomer polyol mixture with a low amine value; then the phosphazene catalyst is used to selectively catalyze the polymerization of low molecular weight polyols to make the molecular weight of the regenerated polyether polyol product more concentrated.

[0014] In the present invention, the step S1 crushes the polyurethane foam material into particles with a diameter less than 5 mm.

[0015] In the present invention, the alcoholysis agent in S1 is one or more of ethylene glycol, glycerol, diethylene glycol, dipropylene glycol, 1,4-butanediol, preferably diethylene glycol and / or dipropylene glycol, more preferably dipropylene glycol, and the base is one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, and cesium hydroxide, preferably potassium hydroxide and / or sodium hydroxide, more preferably potassium hydroxide; preferably, the mass ratio of the alcoholysis agent, the base and the polyurethane foam is (50-500):(1-20):(60-800).

[0016] In the present invention, the alcoholysis temperature is 170-220° C. and the time is 4-8 hours.

[0017] In the present invention, the epoxide in S2 is one or more of ethylene oxide, propylene oxide, and tetrahydrofuran; preferably, the mass ratio of the epoxide to the alcoholysis product is (1-20):1.

[0018] In the present invention, the alkali metal catalyst in S2 is one or more of sodium hydroxide, potassium hydroxide, and cesium hydroxide; preferably, the amount of the alkali metal catalyst is 0.05%-1% of the mass of the alcoholysis product.

[0019] In the present invention, the catalyst A described in S2 is a phosphazene catalyst, preferably one or more of aminotris(dimethylamino)phosphorane chloride, iminotris(dimethylamino)phosphorane, tetrakis(tris(dimethylamino)phosphoranilino)phosphine hydroxide, and dimethylaminotris(tris(dimethylamino)phosphoranilino)phosphine hydroxide; preferably, the amount of the catalyst used is 0.005%-0.05% of the mass of the alcoholysis product.

[0020] In the present invention, the polymerization reaction temperature of S2 is 100-120° C., the first addition of epoxide reaction time is 2-3 hours, and the second addition of epoxide polymerization reaction time is 2-6 hours.

[0021] In the present invention, the neutralizing agent described in S3 is one or more of acetic acid, phosphoric acid, oxalic acid, formic acid, sulfurous acid, and hypochlorous acid.

[0022] In the present invention, the adsorbent described in S3 is one or more of magnesium silicate, aluminum silicate, silica gel, diatomaceous earth, and alumina.

[0023] In the present invention, the neutralization reaction temperature in S3 is 40-60° C., and the reaction time is 0.5-1 h.

[0024] Another object of the present invention is to provide a polyether polyol.

[0025] A polyether polyol is prepared by the waste rigid polyurethane foam recovery method. The polyether polyol has a hydroxyl value of 330-513 mg KOH / g, a viscosity of 1700-4200 cp, an amine value of 0.1-0.5 mg KOH / g, an average molecular weight of 910-3600, and a distribution coefficient of 1.15-1.25.

[0026] Another object of the present invention is to provide a use of a polyether polyol.

[0027] A use of a polyether polyol, wherein the polyether polyol is prepared by the waste rigid polyurethane foam recovery method, or the polyether polyol is used to prepare rigid polyurethane foam for refrigerators and freezers.

[0028] Another object of the present invention is to provide a polyurethane foam.

[0029] A polyurethane foam prepared by using a polyether polyol recycled from waste rigid polyurethane foam, wherein the polyether polyol of the polyurethane foam is prepared by using the waste rigid polyurethane foam recycling method, or using the polyether polyol, or the polyether polyol described in the use of polyether polyol, and the apparent core density of the polyurethane foam is 40-47 mg / m 3 , compression strength 210-229kPa, thermal conductivity 0.021-0.030W / (m·K), water absorption 1.0%-1.1%, closed porosity 95%-99%.

[0030] In one embodiment, the preparation method of polyurethane foam is as follows: weigh recycled polyether, triethylenediamine, and deionized water at room temperature, stir and mix, stir and mix them evenly with PM-200 in a stirrer, and then quickly pour them into a pre-heated aluminum open mold to foam the mixture. After the foaming is completed, take out the foam to obtain polyurethane foam.

[0031] Compared with the prior art, the positive effects of the present invention are:

[0032] The present invention uses two catalysts to be added step by step, and gradually catalyzes the ring-opening polymerization of small molecular amines, residual alcoholysis agents, oligomer polyols and other products after alcoholysis of waste polyurethane materials with epoxides to generate polyether polyols. The method has the advantages that the prepared recovered product has a low amine value (amine value 0.1-0.5 mg KOH / g), a concentrated molecular weight distribution (distribution coefficient 1.15-1.25), and the foam products manufactured from the recovered product have a low thermal conductivity (thermal conductivity 0.021-0.030 W / (m·K)) and high compression strength (210-229 kPa), and can realize high-quality recycling of polyurethane foam. DETAILED DESCRIPTION

[0033] The present invention is further described by the following examples, but the scope of the present invention is not limited to the following examples.

[0034] raw material:

[0035] Rigid polyurethane foam: thermal insulation foam from Haier’s discarded refrigerators;

[0036] Diethylene glycol, MacLean, 98%;

[0037] triethylenediamine, MacLean, AR;

[0038] Potassium hydroxide: McLean, AR;

[0039] Propylene oxide: Wanhua Rongwei;

[0040] Iminotri(dimethylamino)phosphorane: MacLean, 97%;

[0041] Phosphoric acid: Shanghai Titan Technology Co., Ltd., 85%;

[0042] Aluminum silicate: Shanghai Titan, GR;

[0043] Polymeric MDI (PM-200), Wanhua Chemical;

[0044] Test equipment includes:

[0045] Compression testing machine: Shanghai Xieqiang Instrument Manufacturing Co., Ltd., CTM2000 series material testing machine;

[0046] Thermal conductivity tester: Nanjing Huicheng Instrument Co., Ltd., HCDR-S transient plane heat source method thermal conductivity meter.

[0047] Characterization methods:

[0048] Hydroxyl value, Swiss Metrohm 905 Titrando automatic potentiometric titrator, GB / T12008.3-2009;

[0049] Amine value: Titration by perchloric acid method: Use an analytical balance to weigh a certain mass M of the sample to be tested and add it to a conical flask. Then use a pipette to add 15 ml of glacial acetic acid, 5 ml of pure benzene and 1 to 2 drops of indicator crystal violet. Shake well to fully dissolve the sample to be tested. Titrate with a calibrated perchloric acid-acetic acid solution (concentration C). When the solution turns from purple to blue, the titration endpoint is reached, and the volume V consumed by the perchloric acid-acetic acid solution is recorded. The amine value is calculated by the formula (56.1*C*V) / M;

[0050] The average molecular weight was tested by gel permeation chromatography (GPC): 2 drops of the sample to be tested were added into a 2 mL gas phase bottle using a pipette, and then 1.5 mL of dichloromethane was added, and the gas phase bottle was placed into an Agilent 1260II liquid chromatograph for testing.

[0051] Viscosity, Brookfield viscometer DV-II+Pro viscometer, GB / T12008.7-2010;

[0052] Acid value, Swiss Metrohm 905Titrando automatic potentiometric titrator;

[0053] The physical properties of foam products are measured according to GB / T 26689-2011.

[0054] Example 1

[0055] Crush the waste rigid polyurethane foam into particles with a diameter of less than 5mm, add 300g of dipropylene glycol, 1g of potassium hydroxide, and 300g of foam particles into a 2L reactor to compound into an alcoholysis solution. Heat to 180℃ and heat for 8h, then lower the temperature in the reactor to 80℃ and filter to obtain a wine-red alcoholysis product. Add 300g of alcoholysis product to another 2L reactor, add 1.2g of potassium hydroxide as a catalyst, heat to 110℃, and vacuum dehydrate for 1h. Then add 150g of liquid propylene oxide at a feed rate of 2.5g / min, react synchronously during the addition process, and control the temperature at 110℃ for polymerization for 2h. Cool down to 60℃, add 0.06g of iminotri(dimethylamino)phosphorane, stir evenly and heat to 110℃, then add 300g of liquid propylene oxide to the reactor at a feed rate of 2.5g / min, control the temperature at 110℃ for polymerization reaction for 3h, and control the gauge pressure not to exceed 0.4MPa during the reaction. Cool down to 60℃, add 1.5g of phosphoric acid, 6g of pure water, and 0.75g of aluminum silicate in sequence, stir and react for 1h, then heat to 110℃ for vacuum dehydration for 3h, and filter at high temperature to obtain yellow-brown regenerated polyether polyol. During the reaction, the reactor was kept in a nitrogen atmosphere. The characterization results of the polyether polyol are shown in Table 1.

[0056] 80g of recycled polyether, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C) and stirred for 0.5h. After uniform mixing, the mixture was stirred with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0057] Example 2

[0058] The waste rigid polyurethane foam was crushed into particles with a diameter of less than 5mm, and 300g of ethylene glycol, 6g of magnesium hydroxide, and 360g of foam particles were added to a 2L reactor to compound the alcoholysis solution. The temperature was raised to 180℃ and heated for 8h, and then the temperature in the reactor was lowered to 80℃, and the wine-red alcoholysis product was filtered. 300g of alcoholysis product was added to another 2L reactor, and the temperature was raised to 110℃ after adding 3g of potassium hydroxide as a catalyst, and vacuum dehydrated for 1h. Then 150g of liquid propylene oxide was added at a feed rate of 2.5g / min, and the addition process was reacted synchronously, and the temperature was controlled at 110℃ for polymerization reaction for 2h. Cool down to 60℃, add 0.06g of aminotri(dimethylamino)phosphorane chloride, stir evenly and heat to 110℃, and then add 150g of liquid propylene oxide to the reactor at a feed rate of 2.5g / min, and the temperature was controlled at 110℃ for polymerization reaction for 3h. During the reaction, the gauge pressure was controlled not to exceed 0.4MPa. The temperature was lowered to 60°C, 1.5 g phosphoric acid, 6 g pure water, and 0.75 g aluminum silicate were added in sequence, stirred and reacted for 0.5 h, then heated to 110°C for vacuum dehydration for 3 h, and filtered at high temperature to obtain a yellow-brown regenerated polyether polyol. During the reaction, the reactor was kept in a nitrogen atmosphere. The characterization results of the polyether polyol are shown in Table 1.

[0059] 80g of recycled polyether, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C) and stirred for 0.5h. After uniform mixing, the mixture was stirred with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0060] Example 3

[0061] Crush the waste rigid polyurethane foam into particles with a diameter of less than 5mm, add 500g of dipropylene glycol, 20g of potassium hydroxide, and 800g of foam particles into a 2L reactor to compound into an alcoholysis solution. Heat to 220℃ and heat for 4h, then lower the temperature in the reactor to 80℃, filter to obtain a wine-red alcoholysis product. Add 300g of alcoholysis product to another 2L reactor, add 0.15g of potassium hydroxide as a catalyst, heat to 110℃, and vacuum dehydrate for 1h. Then add 2000g of liquid propylene oxide at a feed rate of 20g / min, react synchronously during the addition process, and control the temperature at 110℃ for polymerization for 2h. Cool down to 60℃, add 0.03g of tetrakis(tris(dimethylamino)phosphoramido)phosphine hydroxide, stir evenly and heat to 110℃, then add 150g of liquid propylene oxide to the reactor at a feed rate of 2.5g / min, control the temperature at 110℃ for polymerization for 3h, and control the gauge pressure not to exceed 0.4MPa during the reaction. Cool down to 40℃, add 1.5g of acetic acid, 6g of pure water, and 0.75g of magnesium silicate in sequence, stir and react for 1h, then heat to 110℃ for vacuum dehydration for 3h, and filter at high temperature to obtain yellow-brown regenerated polyether polyol. A nitrogen atmosphere was maintained in the reactor during the reaction. The characterization results of polyether polyols are shown in Table 1.

[0062] 80g of recycled polyether, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C) and stirred for 0.5h. After uniform mixing, the mixture was stirred with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0063] Example 4

[0064] The waste rigid polyurethane foam was crushed into particles with a diameter of less than 5mm, and 200g of diethylene glycol, 1g of potassium hydroxide, and 300g of foam particles were added to a 2L reactor to prepare an alcoholysis solution. The temperature was raised to 220℃ and heated for 4h, and then the temperature in the reactor was lowered to 80℃, and the wine-red alcoholysis product was obtained by filtration. 300g of the alcoholysis product was added to another 2L reactor, and the catalyst 1.5g of sodium hydroxide was added, and the temperature was raised to 110℃, and vacuum dehydration was performed for 1h. Then 300g of liquid ethylene oxide was added at a feed rate of 2.5g / min, and the addition process was reacted synchronously, and the temperature was controlled at 110℃ for polymerization reaction for 3h. Cool down to 60℃, add 0.15g dimethylaminotris(tris(dimethylamino)orthophosphorimino)phosphine hydroxide, stir evenly and heat to 110℃, then add 150g liquid ethylene oxide to the reactor at a feed rate of 2.5g / min, control the temperature at 110℃ for polymerization for 3h, and control the gauge pressure not to exceed 0.4MPa during the reaction. Cool down to 40℃, add 1.5g oxalic acid, 6g pure water, and 0.75g silica gel in sequence, stir and react for 1h, then heat to 110℃ for vacuum dehydration for 3h, and filter at high temperature to obtain yellow-brown regenerated polyether polyol. A nitrogen atmosphere was maintained in the reactor during the reaction. The characterization results of polyether polyols are shown in Table 1.

[0065] 80g of recycled polyether, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C) and stirred for 0.5h. After uniform mixing, the mixture was stirred with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0066] Example 5

[0067] The waste rigid polyurethane foam was crushed into particles with a diameter of less than 5mm, and 300g glycerol, 3g sodium hydroxide, and 500g foam particles were added to a 2L reactor to compound into an alcoholysis solution. The temperature was raised to 220℃ and heated for 4h, and then the temperature in the reactor was reduced to 80℃, and the wine-red alcoholysis product was filtered. 300g of alcoholysis product was added to another 2L reactor, and the temperature was raised to 110℃ after adding the catalyst 1.5g sodium hydroxide, and vacuum dehydration was performed for 1h. Then 300g of liquid ethylene oxide was added at a feed rate of 2.5g / min, and the addition process was reacted synchronously, and the temperature was controlled to polymerize at 110℃ for 3h. Cool down to 60℃, add 0.06g of iminotris(dimethylamino)phosphorane, stir evenly and heat to 110℃, and then add 150g of liquid ethylene oxide to the reactor at a feed rate of 2.5g / min, and the temperature was controlled to polymerize at 110℃ for 3h. During the reaction, the gauge pressure was controlled not to exceed 0.4MPa. The temperature was lowered to 40°C, 1.5 g formic acid, 6 g pure water, and 0.75 g diatomaceous earth were added in sequence, and the mixture was stirred and reacted for 1 h, and then the temperature was raised to 110°C for vacuum dehydration for 3 h. The yellow-brown regenerated polyether polyol was obtained by high-temperature filtration. The nitrogen atmosphere was maintained in the reactor during the reaction. The characterization results of the polyether polyol are shown in Table 1.

[0068] 80g of recycled polyether, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C) and stirred for 0.5h. After uniform mixing, the mixture was stirred with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0069] Comparative Example 1

[0070] Comparative Example 1 is a polyether prepared by adding only alcoholysis agent without adding waste foam, which is compared with Example 1. By comparison, it is found that the low thermal conductivity and high compressive strength of the polyurethane foam product obtained by the scheme of the present invention are related to the alcoholysis structure of the waste foam.

[0071] Add 300g of dipropylene glycol and 1g of potassium hydroxide to a 2L reactor to form a solution. Heat to 180℃ and heat for 8h, then lower the temperature in the reactor to 80℃ and filter to obtain a colorless and transparent product. Add 300g of the product to another 2L reactor, add 1.2g of potassium hydroxide as a catalyst and heat to 110℃, and vacuum dehydrate for 1h. Then add 150g of liquid propylene oxide at a feed rate of 2.5g / min, react synchronously during the addition process, and control the temperature at 110℃ for polymerization for 2h. Cool down to 60℃, add 0.06g of iminotris(dimethylamino)phosphorane, stir evenly and heat to 110℃, then add 300g of liquid propylene oxide to the reactor at a feed rate of 2.5g / min, control the temperature at 110℃ for polymerization for 3h, and control the gauge pressure not to exceed 0.4MPa during the reaction. The temperature was lowered to 60°C, 1.5 g phosphoric acid, 6 g pure water, and 0.75 g aluminum silicate were added in sequence, stirred and reacted for 1 hour, and then heated to 110°C for vacuum dehydration for 3 hours, and filtered at high temperature to obtain colorless and transparent polyether polyol. During the reaction, the reactor was kept in a nitrogen atmosphere. The characterization results of the polyether polyol are shown in Table 1.

[0072] 80g of recycled polyether, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C) and stirred for 0.5h. After uniform mixing, the mixture was stirred with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0073] Comparative Example 2

[0074] Comparative Example 2 uses only solvent for foam degradation, polymerization, neutralization and purification, and is compared with Example 1. By comparison, it is found that the self-degradation without adding alcoholysis agent has the disadvantages of low degradation degree, high amine value of degradation product, low hydroxyl value and wide molecular weight distribution.

[0075] Crush the waste rigid polyurethane foam into particles with a diameter of less than 5mm, add 300g methyl silicone oil as a solvent, 1g potassium hydroxide, and 300g foam particles into a 2L reactor to compound into a reaction solution. Heat to 180℃ and heat for 8h, then lower the temperature in the reactor to 80℃, and filter to obtain a dark wine red degradation product. Add 300g of the degradation product to another 2L reactor, add 1.2g potassium hydroxide as a catalyst, heat to 110℃, and vacuum dehydrate for 1h. Then add 150g of liquid propylene oxide at a feed rate of 2.5g / min, react synchronously during the addition process, and control the temperature at 110℃ for polymerization for 2h. Cool down to 60℃, add 0.06g of iminotri(dimethylamino)phosphorane, stir evenly and heat to 110℃, then add 300g of liquid propylene oxide to the reactor at a feed rate of 2.5g / min, control the temperature at 110℃ for polymerization reaction for 3h, and control the gauge pressure not to exceed 0.4MPa during the reaction. Cool down to 60℃, add 1.5g of phosphoric acid, 6g of pure water, and 0.75g of aluminum silicate in sequence, stir and react for 1h, then heat to 110℃ for vacuum dehydration for 3h, and filter at high temperature to obtain dark brown regenerated polyether polyol. A nitrogen atmosphere was maintained in the reactor during the reaction. The characterization results of polyether polyols are shown in Table 1.

[0076] 80g of recycled polyether, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C) and stirred for 0.5h. After uniform mixing, the mixture was stirred with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0077] Comparative Example 3

[0078] Comparative Example 3 only performs the alcoholysis step, and does not perform the subsequent S2 and S3 steps, and is compared with Example 1. By comparison, it is found that S2 and S3 of the scheme of the present invention reduce the amine value of the recovered polyether, narrow the molecular weight distribution, and there is no residual alcoholysis agent in the recovered polyether.

[0079] Waste rigid polyurethane foam was crushed into particles with a diameter of less than 5 mm, and 300 g of dipropylene glycol, 1 g of potassium hydroxide, and 300 g of foam particles were added to a 2L reactor to prepare an alcoholysis solution. The temperature was raised to 180°C and heated for 8 hours, then the temperature in the reactor was lowered to 80°C, and a wine-red alcoholysis product was obtained by filtration. The characterization results of the polyether polyols are shown in Table 1.

[0080] 80g of alcoholysis product, 2.4g of triethylenediamine and 8g of deionized water were weighed at room temperature (25°C), stirred and mixed for 0.5h, and after being uniformly mixed, they were stirred and mixed with 120g of PM-200 in a stirrer (rotation number 3000rpm) for 6 seconds, and then quickly poured into an aluminum open mold (size: 300mm long, 300mm wide, 50mm thick) preheated to 60°C to foam the mixture. After 7 minutes, the foam was taken out to obtain polyurethane foam. The characterization results of the polyurethane foam are shown in Table 2.

[0081] Table 1 Comparative Examples and Examples Regenerated Polyether Polyol Index Analysis

[0082]

[0083] From Example 1 and Comparative Example 1 in Table 1, compared with the polyether polyol obtained by alcoholysis, polymerization, neutralization and purification without adding waste rigid foam, the regenerated polyether polyol obtained by the present invention has a larger average molecular weight and a smaller molecular weight distribution coefficient. From Example 1 and Comparative Example 1 in Table 2, the foam product made of the regenerated polyether polyol obtained by the present invention has a lower thermal conductivity and a higher compressive strength.

[0084] From Example 1 and Comparative Example 2 in Table 1, compared with the polyether polyol obtained by only using a solvent to degrade polyurethane foam, polymerize, and neutralize and purify, the regenerated polyether polyol obtained by the present invention has a lower amine value and a smaller molecular weight distribution coefficient;

[0085] From Example 1 and Comparative Example 3 in Table 1, compared with the polyether polyol obtained by only alcoholysis of polyurethane foam, the regenerated polyether polyol obtained by the present invention has a lower amine value, a larger molecular weight, a smaller molecular weight distribution coefficient, and no small molecule alcoholysis agent residue.

[0086] Table 2 Comparative Examples and Examples Analysis of Polyurethane Rigid Foam Indexes Prepared by Regenerated Polyether Polyols

[0087]

[0088] It can be seen from the results of the examples in Table 2 that the polyurethane rigid foam prepared by the recycled polyether polyol obtained by the method of the present invention has the characteristics of low thermal conductivity and high compression strength, and fully meets the performance requirements for the recycling of rigid polyurethane foam for refrigerators and freezers.

[0089] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing polyether polyol by recycling waste rigid polyurethane foam, characterized in that: The method comprises the following steps: S1: crushing the recovered rigid polyurethane foam material into particles, compounding with an alcoholysis agent and an alkali to form an alcoholysis solution, and heating to obtain an alcoholysis product; S2: filtering the alcoholysis product and transferring it to a reactor, adding an alkali metal catalyst, adding epoxide after dehydration to carry out polymerization reaction, cooling, then adding catalyst A, heating and continuing to add epoxide to carry out polymerization reaction to obtain a high molecular weight polyether polyol; S3: Cooling the polyether polyol, adding a neutralizer and an adsorbent, dehydrating after neutralization reaction, and filtering to obtain the target polyether polyol; Wherein, the amount of the alkali metal catalyst in S2 is 0.05%-1% of the mass of the alcoholysis product; Wherein, the A catalyst in S2 is a phosphazene catalyst, and the A catalyst is one or more of aminotris(dimethylamino)phosphorane chloride, iminotris(dimethylamino)phosphorane, tetrakis(tris(dimethylamino)phosphoranilino)phosphine hydroxide, and dimethylaminotris(tris(dimethylamino)phosphoranilino)phosphine hydroxide; the amount of the A catalyst used is 0.005%-0.05% of the mass of the alcoholysis product.

2. The method according to claim 1, characterized in that S1 crushes the polyurethane foam material into particles with a diameter less than 5 mm; And / or, the alcoholysis agent in S1 is one or more of ethylene glycol, glycerol, diethylene glycol, dipropylene glycol, 1,4-butanediol, and the base is one or more of sodium hydroxide, potassium hydroxide, magnesium hydroxide, and cesium hydroxide; And / or, the alcoholysis temperature is 170-220° C., and the time is 4-8 hours.

3. The method according to claim 2, characterized in that S1: the alcoholysis agent is diethylene glycol and / or dipropylene glycol, and the base is potassium hydroxide and / or sodium hydroxide; The mass ratio of the alcoholysis agent, the alkali and the polyurethane foam is (50-500):(1-20):(60-800).

4. The method according to claim 3, characterized in that S1: the alcoholysis agent is dipropylene glycol, and the alkali is potassium hydroxide.

5. The method according to claim 1, characterized in that S2 The epoxide is one or more of ethylene oxide, propylene oxide, and tetrahydrofuran; And / or, the alkali metal catalyst in S2 is one or more of sodium hydroxide, potassium hydroxide, and cesium hydroxide; And / or, the polymerization reaction temperature in S2 is 100-120° C., the first addition of epoxide polymerization reaction time is 2-3 hours, and the second addition of epoxide polymerization reaction time is 2-6 hours.

6. The method according to claim 5, characterized in that The mass ratio of epoxide to alcoholysis product in S2 is (1-20):

1.

7. The method according to claim 1, characterized in that S3 The neutralizing agent is one or more of acetic acid, phosphoric acid, oxalic acid, formic acid, sulfurous acid, and hypochlorous acid; And / or, the adsorbent in S3 is one or more of magnesium silicate, aluminum silicate, silica gel, diatomaceous earth, and alumina; And / or, the neutralization reaction temperature in S3 is 40-60° C., and the reaction time is 0.5-1 h.

8. A polyether polyol, prepared by the method according to any one of claims 1 to 7, characterized in that: The polyether polyol has a hydroxyl value of 330-513 mg KOH / g, a viscosity of 1700-4200 cp, an amine value of 0.1-0.5 mg KOH / g, an average molecular weight of 910-3600, and a distribution coefficient of 1.15-1.

25.

9. Use of a polyether polyol, wherein the polyether polyol is prepared by the method according to any one of claims 1 to 7, or the polyether polyol according to claim 8, characterized in that: The polyether polyol is used for preparing rigid polyurethane foam for refrigerators and freezers.

10. A polyurethane foam prepared by using a polyether polyol recycled from waste rigid polyurethane foam, wherein the polyether polyol of the polyurethane foam is prepared by the method according to any one of claims 1 to 7, or by using the polyether polyol according to claim 8, or by being the polyether polyol described in the use of polyether polyol according to claim 9, characterized in that: The apparent core density of the polyurethane foam is 40-47 mg / m 3 , compression strength 210-229kPa, thermal conductivity 0.021-0.030W / (m·K), water absorption 1.0%-1.1%, closed porosity 95%-99%.

Citation Information

Patent Citations

  • Image processing apparatus, image processing method, and program

    CN102196279A

  • Method of preparing polyurethane thermal insulation material by recovering waste polyurethane elastomer

    CN104672414A

  • Polyurethane foam chemical recovery method

    CN105399985A

  • Method for recycling waste polyurethane product

    CN104693397A